The STUDI KOMPARATIF KINERJA DOSEN BERSTATUS PABBAJITA DENGAN GHARAVĀSA DI SEKOLAH TINGGI AGAMA BUDDHA (STAB) KERTARAJASA - Wina Dhamayanti; Titik Hartini; Adji Sastrosupadi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
STAB Kertajasa is a Buddhist college which has two types of lecturer status, namely lecturer with the status of pabbajita and gharavāsa. The purpose of this study was to determine the differences in the performance of lecturers with the status of pabbajita and gharavāsa. The research design used was a survey form. The instrument used in this study was a questionnaire distributed to 27 second semester students and 27 semester VI students. Data were tabulated and analyzed using a Likert scale and t-test. The results of this study indicate that the second semester lecturers generally get higher performance scores than gharavāsa. Acquisition of values ​​on a continuum line said that lecturers with the status of pabbajita received the criteria for SB (Very Good), while those with status of gharavāsa ranged from B (Good) to SB (Very Good) with a total score and percent of achievement of each lecturer, namely 1803 (89.04%) for lecturers A, 1759 (86.86%) for lecturers B, 1637 (80.84%) for lecturers D, and 1597 (77.96%) for lecturers C. gharavāsa has performance with the criteria of SB (Very Good) which has a total score and percent of achievement, namely 1901 (93.88%) for lecturer E, 1759 (86.86%) for lecturer F, 1642 (81.09%) for lecturer G , and 1812 (89.48%) for lecturers H. The difference in performance between lecturers with the status of pabbajita and gharavāsa semester II is in real areas and semester IV lecturers have very real differences. From this research, it is hoped that it can improve the performance of lecturers so that STAB Kertarajasa becomes better by having good quality lecturer performance.